Strengthening the University-Maritime Industry Collaborations (UMICs): Technology Issues - Ummu Ajirah Abdul Rauf; Nusra Izzaty Aziz; Nor Amirah Syairah Zulkarnaini; Mazzlida Mat Deli; Maryam Jamilah Asha’ari; ‘Ainul Huda Jamil; Siti Intan Nurdiana Wong Abdullah (Journal of Applied Engineering and Technological Science (JAETS), 2023)
In management practise and research, the university-maritime industry collaborations (UMICs) have grown in significance. This trend is reinforced by the necessity for innovation in the current industry environment and the desire of policymakers to commercialise knowledge from academia. Much less is known about these collaborations, although significant research efforts have been made to identify the success factors for these collaborations. Therefore, the aim of this study is to identify and explore the key factors that strengthen UMICs and propose a framework to enhance collaboration, so that a research agenda for the future will be developed based on an assessment of the existing literature. This study adopted a method of systematic literature review using published and unpublished theoretical literature to conduct analysis using five research databases in order to propose a framework aimed at identifying the key factors to strengthen UMICs. The findings of this study concluded that effective communication, trust, and adequate fund resources are essential for UMICs to succeed. Open communication channels, mutual trust, and shared vision can help build strong partnerships, while adequate funding can support research and development of new technologies, practices, and solutions. Based on previous research, none of them treated combined fund resources, effective communication, and trust as an independent variables towards UMICs relationship specifically. Hence, this study fills the gap by proposing a framework to test the relationship between fund resources, effective communication, and trust towards UMICs. Thus, the proposed framework can be used as a benchmark to strengthen UMICs in the future. This study also will encourage the managers in the maritime industry to drive innovation, establish strategic collaborations, actively involve stakeholders, and foster innovation and economic growth in the maritime industry to strengthen UMICs. The existing limited body of knowledge and literature will also benefit from this study.